Territory quality differs between paired and unpaired male Common Redstarts Phoenicurus phoenicurus. Issue 2 (3rd April 2019) - Moser, Valentin; Spaar, Reto; Meichtry-Stier, Kim; Martinez, Nicolas
ABSTRACT: We compared habitat characteristics between territories of paired and unpaired males of the long-distance migratory Common Redstart Phoenicurus phoenicurus . Nesting possibilities and reachable sparse vegetation were more abundant in territories of paired males, clearly highlighting the importance of both parameters when implementing habitat enhancements for the species.